Predictors of disparities in retention in care among African Americans living with HIV. Issue 1 (2nd January 2021) - Anderson, Ashley N.; Haardörfer, Regine; McDonnell Holstad, Marcia; Nguyen, Minh Ly T.; Waldrop-Valverde, Drenna
ABSTRACT: Limited health literacy may contribute to racial disparities in retention in HIV care. The purpose of this study was to evaluate the effects of health literacy and patient and social-level factors on retention in care among African Americans living with HIV. This study included 699 participants recruited from outpatient HIV clinics and retention in care was defined as visit adherence. Multivariable logistic regression models were used to assess predictors of visit adherence among persons with 100% visit adherence compared to less than 100% visit adherence. Controlling for demographic factors, the odds of 100% visit adherence was greater among non-African Americans compared to African Americans. In models that included health literacy, race was no longer significant and health literacy was a significant predictor of 100% visit adherence. Among participants with less than 100% visit adherence, health literacy was not a significant predictor of visit adherence; however, age, marital status, and patient attitudes towards the health care provider were significant predictors. Findings suggest that health literacy may mediate the relationship between race and visit adherence. Future studies should further examine these relationships and develop interventions that target modifiable factors, with a goal of improving health equity and minimizing disparities.